Sulfur-vacancy-rich ZnIn2S4-coated FeNi0. 48S1.71 heterojunction photocatalyst as well as preparation method and application thereof

By growing sulfur-rich vacancies on the surface of FeNi0.48S1.71 hollow nanospheres in situ, forming an S-type heterojunction composite material, solving the problem of severe photocarrier composite and low mobility in photocatalytic hydrogen production materials. , achieving efficient photocatalytic hydrogen production and antibiotic degradation.

CN119406430APending Publication Date: 2025-02-11CHENGDU TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411558990.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing photocatalytic hydrogen-producing composite materials have problems such as severe photocarrier recombination, low mobility and slow interface reaction rates, and it is difficult to take into account the high hydrogen yield and antibiotic degradation efficiency.

Method used

By growing sulfur-rich vacancies ZnIn2S4 nanosheets in situ on the surface of FeNi0.48S1.71 hollow nanospheres, an S-type heterojunction composite material with a three-dimensional core-shell hollow structure is formed, and the synergistic effect of sulfur vacancies and heterojunctions is used to improve loading Flow separation and mobility.

Benefits of technology

Low photogenerated carrier recombination, higher mobility and interface reaction rate are achieved, photocatalytic hydrogen production and antibiotic degradation efficiency are improved, and excellent photocatalytic performance is shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406430A_ABST
    Figure CN119406430A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-rich vacancy ZnIn2S4 at FeNi < 0.48 > S < 1.71 > heterojunction photocatalyst as well as a preparation method and application thereof, and the photocatalyst is a sulfur-rich vacancy ZnIn2S4 at FeNi < 0.48 > S < 1.71 > heterojunction composite material with a hollow structure, which is formed by in-situ growth of a sulfur-vacancy-containing ZnIn2S4 nanosheet on the surface of a FeNi < 0.48 > S < 1.71 > hollow nanosphere. The photocatalyst provided by the invention has a larger specific surface area and a wider light absorption range, and the internal sulfur vacancy as an electron capture center can inhibit the compounding of photo-induced electron-hole pairs. The three-dimensional core-shell hollow sphere structure can reduce the recombination rate of charges, improve the mobility of electrons, show better photocatalytic performance, and have great application prospects in the fields of energy and environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a sulfur-rich ZnIn2S4@FeNi 0.48 S 1.71 Heterojunction photocatalyst and its preparation method and application. Background Art

[0002] Antibiotics are the most commonly used antibacterial drugs in clinical practice, but they are difficult to degrade. If they are not properly disposed of, they will cause environmental problems. Hydrogen energy, as the most ideal pollution-free green energy, has received great attention from researchers. Photocatalytic technology using solar energy is considered to be one of the most promising technologies to solve energy (photocatalytic hydrogen production) and environmental problems (antibiotic degradation). In order to effectively use sunlight for photocatalytic hydrogen production and antibiotic degradation, the band gap of the photocatalyst should be less than 3eV. The valence band of metal sulfides is usually composed of shallow S 3p orbitals, which means that they have a smaller band gap. Among these ternary metal sulfides, ZnIn2S4 is a visible light responsive layered structure photocatalytic material, which will give it a more unique electronic structure and photoelectric properties. Although ZnIn2S4 has good crystallinity and photoelectric properties, it still has problems such as narrow light absorption range, severe carrier recombination, low mobility and slow interface reaction rate.

[0003] In the photocatalytic system, there are three main steps for photocatalysts to carry out efficient photocatalytic reactions: (1) light excitation to generate photogenerated carriers; (2) migration of photogenerated carriers; and (3) redox reactions on the surface of the material. Therefore, people currently develop and design corresponding ZnIn2S4 modification strategies based on these three aspects, such as element doping, deposition of co-catalysts, construction of vacancy defect engineering, and construction of heterojunctions. However, a single modification strategy still cannot meet all the necessary conditions for various photocatalytic redox reactions.

[0004] In order to improve the photocatalytic efficiency, some people have used multi-strategy synergistic modification, such as the article "Sulfur-Deficient ZnIn2S4 / Oxygen-Deficient WO3 Hybrids with Carbon Layer Bridges as a Novel Photothermal / Photocatalytic Integrated System for Z-Scheme OverallWater Splitting" published by Yijin Wang, Wenjing Huang, Shaohui Guo et al. in Advanced Energy Materials in 2021, which used sulfur vacancy ZnIn2S4 and oxygen vacancy WO3 to obtain a photocatalytic composite material. However, this material can only catalyze hydrogen production, but cannot degrade antibiotics. The inventor of this patent and his research and development team published "Fast charge transfer kinetics in Sv-ZnIn2S4 / Sb2S3 S-schemeheterojunction photocatalyst for enhanced photocatalytic hydrogen evolution" in RareMetals in 2023. They used the synergistic modification strategy of sulfur vacancies and heterojunctions to obtain ZnIn2S4 / Sb2S3 composite materials with a hydrogen production capacity of 2741.3μmol·g -1 ·h -1 However, this composite material still has serious problems of photogenerated carrier recombination and low mobility.

[0005] In the face of many problems existing in current photocatalytic hydrogen production composite materials, it is necessary to strive to develop and research a composite material with lower photogenerated carrier recombination, higher mobility and interfacial reaction rate, as well as higher hydrogen production and antibiotic degradation efficiency.

[0006] In view of this, this patent application is filed. Summary of the invention

[0007] In order to solve the many problems existing in the photocatalytic hydrogen production composite materials, the present invention provides a sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71 A heterojunction photocatalyst, and also a preparation method and application thereof are provided.

[0008] The first object of the present invention is to provide a sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71Heterojunction photocatalysts are prepared by in situ growth of ZnIn2S4 nanosheets containing sulfur vacancies on FeNi 0.48 S 1.71 On the surface of hollow nanospheres, sulfur-rich vacancies ZnIn2S4@FeNi with hollow structures are formed. 0.48 S 1.71 Heterojunction composite materials.

[0009] The present invention utilizes sulfur-rich pores of ZnIn2S4 nanosheets to grow in situ on FeNi 0.48 S 1.71 On the surface of the hollow nanosphere, an S-type heterojunction composite material with a three-dimensional core-shell hollow structure is formed, which has a larger specific surface area and a wider light absorption range, and the internal sulfur vacancies can act as electron capture centers to inhibit the recombination of photogenerated electron-hole pairs. In addition, the S-type heterojunction formed at the interface not only promotes carrier separation, but also retains the strong reduction and oxidation capabilities of electrons and holes. At the same time, when the three-dimensional core-shell hollow sphere structure of the present invention is used, the electrons only need to migrate outward from the spherical shell, and the electron migration distance is greatly shortened, which reduces the charge recombination rate and improves the electron mobility, thereby showing better photocatalytic performance, and has great application prospects in the fields of energy and environment.

[0010] In order to construct heterojunctions, it is necessary to find semiconductor materials with suitable band gaps and band edges. Iron-nickel sulfide ternary metal sulfides have been widely studied in the fields of supercapacitors and lithium-ion batteries. The band gaps and morphologies of iron-nickel sulfides in the currently disclosed technologies vary, such as flaky Fe5Ni4S8 materials, granular FeNiS x Composited with g-C3N4 for photocatalytic degradation of tetracycline hydrochloride. Therefore, nickel iron sulfide is expected to be composited with ZnIn2S4 to form a heterojunction material for photocatalytic hydrogen production. However, the inventors found through research that the existing nickel iron sulfide materials and ZnIn2S4 have many problems such as small specific surface area, serious photogenerated carrier recombination, and low electron mobility. Therefore, in the present invention, the inventors creatively introduced morphology control into the sulfur vacancy and heterojunction strategy, and introduced the concepts of morphology control, sulfur vacancies and heterojunctions into a system to form a synergy, and obtained FeNi 0.48 S 1.71 This unique component was used to obtain nanospheres with hollow structures as carriers, on which ZnIn2S4 nanosheets rich in sulfur vacancies were in situ grown, and a three-dimensional core-shell hollow sphere composite structure was obtained.

[0011] In an optional embodiment, the size of the ZnIn2S4 nanosheet is 200-1000 nm, and the thickness of the nanosheet is 15-25 nm;

[0012] And / or, the FeNi 0.48 S1.71 The size of the hollow nanospheres is 300 to 1000 nm, and the hollowing degree of the hollow nanospheres (inner pore size / nanosphere diameter) is 85% to 90%;

[0013] And / or, the size of the photocatalyst is 500-2000 nm.

[0014] The second object of the present invention is to provide any of the above sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71 A method for preparing a heterojunction photocatalyst comprises:

[0015] Preparation of FeNi 0.48 S 1.71 Hollow nanospheres: Using ferrous chloride tetrahydrate, nickel chloride hexahydrate, polyvinyl pyrrolidone, sulfur powder and thiourea as raw materials, react at 120-150°C for 6-9 hours to obtain black powder, and then calcine the black powder under inert gas protection, keep it at 320-350°C for 3-4 hours, then heat it to 580-610°C and keep it for 3-4 hours to obtain FeNi 0.48 S 1.71 Hollow nanosphere materials;

[0016] FeNi 0.48 S 1.71 The hollow nanospheres were added to the acid solution, followed by zinc chloride, indium chloride tetrahydrate and thioacetamide to obtain a solid-liquid mixture, which was reacted at 80-90°C for 2-3h in an oil bath to obtain sulfur-rich vacancy ZnIn2S4@FeNi with a hollow structure. 0.48 S 1.71 Heterojunction photocatalytic materials.

[0017] The present invention adopts a one-step oil bath method for in-situ growth, which can provide a specific thermal environment by using the oil bath, and the temperature control is more precise and uniform, and the reaction conditions can be better maintained, which is more conducive to improving the efficiency of in-situ growth, so that ZnIn2S4 can grow more quickly and uniformly on the carrier, and a composite material with better crystallinity can be obtained; and this one-step oil bath method for in-situ growth is more conducive to enhancing the active material ZnIn2S4 and FeNi 0.48 S 1.71 The interface interaction between them forms a tighter bond, which is critical for improving the performance stability and synergistic effect of composite materials in photocatalytic applications. At the same time, the one-step oil bath in-situ growth method of the present invention simplifies the process flow, which is more convenient than some in-situ growth methods that require multiple steps and may involve complex processing in the middle.

[0018] At the same time, the present invention performs gradient heating when preparing hollow nanospheres, and initially forms a hollow structure at a low temperature (100-500°C), but at this time the crystallinity is relatively low and the grain size is small, and then uses a higher temperature (500-800°C) to increase the grain size of the material, and the hollow structure is more stable and regular. If a high temperature of 500-800°C is used directly without a gradient heating method, the material will experience a large temperature change in a short time, resulting in material instability, cracks, etc.

[0019] The reaction is carried out at 120-150° C. for 6-9 hours in order to take into account both the size of the formed spherical particles and the space of the internal hollow structure.

[0020] In the second stage, the calcination in a tubular furnace at a temperature of 320-350°C for 3-4 hours is to ensure the integrity of the hollow structure and make the course structure more uniform and dense, so as to obtain a hollow spherical structure with stable structure and good consistency.

[0021] The third stage is calcined in a tubular furnace at a temperature of 580-610°C for 3-4 hours to ensure that the structure of the hollow material is fully solidified and stabilized, and the shell of the material will not be loose or have uneven porosity.

[0022] The calcination temperature and time and the gradient reaction selected in this patent result in the final formation of a FNS material with a hollow sphere structure.

[0023] The present invention is used to prepare FeNi 0.48 S 1.71 When preparing hollow nanospheres, a tubular furnace calcination method is used, and the hollow structure of the prepared hollow nanospheres is more uniform.

[0024] In an optional embodiment, FeNi is prepared 0.48 S 1.71 When preparing hollow nanospheres, first dissolve ferrous chloride tetrahydrate and nickel chloride hexahydrate in ethylene glycol, stir and dissolve to obtain solution ①;

[0025] Then add polyvinyl pyrrolidone to solution ①, dissolve by ultrasonication and stirring to obtain solution ②;

[0026] Add sulfur powder and thiourea to solution ②, stir and dissolve to obtain solution ③;

[0027] The solution ③ is reacted at 120-150°C for 6-9h, cooled naturally, centrifuged, washed and dried to obtain a black powder.

[0028] In an optional embodiment, the molar ratio of ferrous chloride tetrahydrate to nickel chloride hexahydrate is 3:(1-1.5), and the concentration of metal ions in the solution ① is 0.05-0.1 mol / L.

[0029] In an optional embodiment, the average molecular weight of the polyvinyl pyrrolidone is 40,000, and the content of polyvinyl pyrrolidone in the solution ② is 5 to 10 g / L.

[0030] In an optional embodiment, the molar ratio of iron ions, nickel ions, sulfur powder and thiourea in solution ③ is 3: (1-1.5): (1-3.5): (4.5-7).

[0031] The inventor selected the ratio of iron source and nickel source. When the ratio of Fe source is relatively high, the crystal growth rate of the material will be accelerated, which will eventually lead to the overall size of the material being larger, while the Ni source can make the crystal growth more orderly and the crystallinity better. Therefore, considering the overall size and crystallinity of the material, the ratio described in this patent is adopted. The significance of the metal ion concentration range of 0.05-0.1 mol / L in the solution: if the concentration is low, the size of the spherical particles formed is usually small, so that ZnIn2S4 nanosheets with a size of several hundred nanometers cannot be grown in situ thereon. If the concentration is high, the nucleation process in the reaction system is very rapid, and a large number of nuclei grow at the same time, which is prone to overgrowth and agglomeration. This makes the morphology of the ball difficult to control and the structural stability is also affected. The reason for selecting a polyvinyl pyrrolidone concentration of 5-10 g / L: Polyvinyl pyrrolidone is added in this patent as a surfactant, which can reduce the surface tension of the solution, make the particles in the reaction system more stably dispersed in the solution, and prevent the agglomeration of particles.

[0032] At the same time, the sulfur sources in the present invention include thiourea and sulfur powder. The main function of thiourea is to slowly release sulfur ions, which helps to control the reaction rate, so that metal ions and sulfur ions can be evenly combined, which is conducive to forming a regular spherical morphology. Sulfur powder directly provides sulfur elements and reacts quickly with metal ions to form metal sulfides. Therefore, in the ratio of (1 to 3.5): (4.5 to 7) between the two, sulfur powder is always less than thiourea, which ensures that the release rate of sulfur ions in the reaction system is not too fast or too slow.

[0033] In an optional embodiment, the heating rate during calcination of the black powder is 3-6° C. / min.

[0034] In an optional embodiment, the pH value of the acid solution is 2-4, and the FeNi 0.48 S 1.71 The mass ratio of zinc chloride to indium chloride is (0.3-1):2, and the amount ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:2:(4.5-16).

[0035] Thioacetamide provides a sulfur source for the reaction system in the form of H2S gas under acidic conditions and reacts with Zn 2+ 、In 3+The reaction combines to generate ZnIn2S4. If the pH value is too low, it means that the solution is too acidic, which makes the S source release too fast, which will lead to the formation of ZnIn2S4 nanosheets too fast and poor crystallinity. On the contrary, if the pH value is too high, it means that the solution is too acidic, which makes the S source release too slow, resulting in increased time cost.

[0036] The present invention selects FeNi 0.48 S 1.71 The mass ratio of ZnIn2S4 to zinc chloride is (0.3-1):2. This is because if the proportion of ZnIn2S4 in the composite material is too high, a shielding effect will occur, that is, too many ZnIn2S4 nanosheets will shield each other and block the FeNi 0.48 S 1.71 Absorption of light. If the proportion of ZnIn2S4 is too low, the utilization rate of light is not high.

[0037] The ratio of the amount of zinc chloride, indium chloride tetrahydrate and thioacetamide is selected because the sulfur source used in this patent is thioacetamide, and the mechanism of its sulfur source release is that thioacetamide releases H2S in an acidic solution, and H2S dissolves in water and decomposes S 2- , and then combines with Zn and In to form ZnIn2S4. In this process, the S source will volatilize in the form of H2S and cause certain losses. Therefore, the amount of thioacetamide added should be slightly excessive, but not too much, because excess S may react with other elements or compounds to generate some unwanted impurity phases. The presence of these impurities will affect the performance of the photocatalytic material. The presence of impurity phases may also change the crystal structure and electronic structure of the material, thereby affecting the active sites and charge transfer process of the photocatalytic reaction. On the other hand, the reason why thioacetamide is chosen as the S source instead of the common Na2S is that the release rate of the S source should not be too fast or too slow. If it is too fast (Na2S is dissolved in water, it will quickly and completely ionize to produce S 2- ) will result in the formation rate of ZnIn2S4 nanosheets being too fast and the crystallinity being poor.

[0038] Preferably, FeNi is prepared 0.48 S 1.71 For hollow nanospheres, the reaction is carried out at 120-150°C for 6-9 hours, then naturally cooled, centrifuged, washed and dried; the solid-liquid mixture is reacted at 80-90°C for 2-3 hours in an oil bath, then naturally cooled, washed and dried;

[0039] The washing is to use deionized water and anhydrous ethanol to wash the sample alternately for 3 times or more, the drying temperature is 60-90° C., and the drying time is 8-12 hours.

[0040] The third object of the present invention is to provide the use of any of the above catalysts in photocatalytic decomposition of water to produce hydrogen and degrade organic pollutants. The organic pollutant is preferably tetracycline hydrochloride.

[0041] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0042] 1. The present invention cleverly designs FeNi 0.48 S 1.71 Materials, and FeNi with hollow sphere structure was prepared 0.48 S 1.71 Semiconductor nanomaterials, ZnIn2S4 nanosheets containing sulfur vacancies were then grown in situ on the FeNi substrate using a one-step oil bath method. 0.48 S 1.71 An S-type heterojunction composite material is formed on the hollow nanospheres, which greatly shortens the electron migration distance, reduces the charge recombination rate, and improves the electron mobility. Under the synergistic effect of the S-type heterojunction and sulfur vacancies, the composite sample exhibits excellent photocatalytic hydrogen production and tetracycline hydrochloride degradation performance.

[0043] 2. The sulfur-rich vacancy ZnIn2S4@FeNi with special spatial structure of the present invention 0.48 S 1.71 Composite materials not only have 84.1m 2 / g has a larger specific surface area (sulfur-rich ZnIn2S4 is 28.1m 2 / g), a wider light absorption range of 400-850nm (400-550nm for sulfur-rich ZnIn2S4), and the internal sulfur vacancies as electron capture centers can inhibit the recombination of photogenerated electron-hole pairs. In addition, the S-type heterojunction formed at the interface not only promotes carrier separation, but also retains the strong reduction and oxidation capabilities of electrons and holes. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0045] Figure 1 It is the electron spin resonance spectrum (ESR) of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 3 of the present invention; the abscissa Magnetic field is the magnetic field intensity.

[0046] Figure 2These are scanning electron microscope (SEM) morphology images of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 8 of the present invention, wherein (a), (b), (c), (d), (e), (f), (g), (h) and (i) are SEM images of the photocatalytic materials prepared in Comparative Examples 6 to 8, Comparative Examples 1 to 4, Example 1 and Comparative Example 5, respectively.

[0047] Figure 3 This is the energy dispersive spectrum (EDS) of the photocatalytic material prepared in Example 1 of the present invention.

[0048] Figure 4 The morphology and element distribution diagram of the photocatalytic material prepared in Example 1 of the present invention, wherein (a), (b) and (c) are transmission electron microscopy (TEM), element distribution diagram and high-resolution transmission electron microscopy (HRTEM) morphology diagram of the photocatalytic material prepared in Example 1, respectively; "S vacancies" in (c) represent S vacancies.

[0049] Figure 5 The photocatalytic performance graphs of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 5, wherein (a) and (b) are the photocatalytic hydrogen production and tetracycline hydrochloride degradation curves of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 5, respectively;

[0050] Figure 6 X-ray diffraction (XRD) patterns of photocatalytic hydrogen production and tetracycline hydrochloride degradation before and after the photocatalytic material prepared in Example 1; After H2evolution in the figure represents after hydrogen production, and After TCH degradation represents after tetracycline hydrochloride degradation. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0052] Embodiment 1:

[0053] This embodiment provides a hollow structure of sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71 The preparation method of the heterojunction photocatalyst comprises the following steps:

[0054] S1. Dissolve 4.2mmol ferrous chloride tetrahydrate and 1.4mmol nickel chloride hexahydrate in 60mL ethylene glycol and stir to dissolve to obtain solution ①;

[0055] S2. Add 0.3 g of polyvinyl pyrrolidone (average molecular weight 40,000) to solution ①, dissolve by ultrasonication and stirring to obtain solution ②;

[0056] S3. Add 2.8mmol sulfur powder and 8.4mmol thiourea to solution ②, stir and dissolve to obtain solution ③;

[0057] S4. The solution ③ was transferred to a reactor, reacted at 120-150°C for 6-9h, cooled naturally and centrifuged, the sample was washed alternately with deionized water and anhydrous ethanol 5 times, and dried in a vacuum oven at 60-90°C for 8-12h to obtain a black powder;

[0058] S5. Put the above black powder into a ceramic boat and place it in a tube furnace filled with argon gas, keep it at 320℃ for 3h, then increase the temperature to 580℃ at 3℃ / min and keep it for 4h. Cool naturally to obtain FeNi 0.48 S 1.71 Hollow nanosphere materials;

[0059] S6. Add 21.2 mg of FeNi to a dilute hydrochloric acid solution with a pH of 3. 0.48 S 1.71 The material was ultrasonically dispersed, and then 0.5mmol zinc chloride, 1mmol indium chloride tetrahydrate and 4mmol thioacetamide were added, and ultrasonic stirring was performed to obtain a solid-liquid mixture;

[0060] S7. The solid-liquid mixture was transferred to a three-necked flask by a one-step solvothermal method. The flask was then placed in an oil bath and heated to 80 °C and stirred for 3 h. After natural cooling, the sample was centrifuged and washed alternately with deionized water and anhydrous ethanol for 5 times. The sample was dried in a vacuum oven at 60-90 °C for 8-12 h to obtain the sulfur-rich ZnIn2S4@FeNi with a hollow structure. 0.48 S 1.71 Heterojunction photocatalytic materials.

[0061] Comparative Example 1:

[0062] This comparative example provides a hollow structure FeNi 0.48 S 1.71 The method for preparing the photocatalyst is different from that of Example 1 in that only steps S1 to S5 are retained, while steps S6 to S7 are omitted.

[0063] Comparative Example 2:

[0064] This comparative example provides a method for preparing an untreated ZnIn2S4 photocatalyst, which differs from Example 1 in that only steps S6 to S7 are retained, and step S6 does not add FeNi 0.48 S 1.71The materials were modified and the amount of thioacetamide was changed to 2 mmol, while the other steps and parameters remained unchanged.

[0065] Comparative Example 3:

[0066] This comparative example provides a method for preparing a sulfur-vacancy-rich ZnIn2S4 photocatalyst, which differs from comparative example 2 in that the amount of thioacetamide in step S6 is changed to 4 mmol, and the remaining steps and parameters remain unchanged.

[0067] Comparative Example 4:

[0068] This comparative example provides a hollow structure of sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71 The preparation method of heterojunction photocatalyst is different from that of Example 1 in that: FeNi 0.48 S 1.71 The amount was changed to 10.6 mg, and the other steps and parameters remained unchanged.

[0069] Comparative Example 5:

[0070] This comparative example provides a hollow structure of sulfur-rich vacancy ZnIn2S4@FeNi 0.48 S 1.71 The preparation method of heterojunction photocatalyst is different from that of Example 1 in that: FeNi 0.48 S 1.71 The amount was changed to 31.8 mg, and the other steps and parameters remained unchanged.

[0071] Comparative Example 6:

[0072] This comparative example provides a black spherical structure of FeNi x S y The method for preparing the photocatalyst precursor is different from that of Example 1 in that the amounts of ferrous chloride tetrahydrate and nickel chloride hexahydrate in step S1 are changed to 4.9 mmol and 0.7 mmol respectively, and steps S2 to S4 are retained, but steps S6 to S7 are omitted.

[0073] Comparative Example 7:

[0074] This comparative example provides a black spherical structure of FeNi 0.48 S 1.71 The method for preparing the photocatalyst precursor is different from that of Example 1 in that only steps S1 to S4 are retained, while steps S5 to S7 are omitted.

[0075] Comparative Example 8:

[0076] This comparative example provides a black spherical structure of FeNi m S nThe method for preparing the photocatalyst precursor is different from that of Example 1 in that the amounts of ferrous chloride tetrahydrate and nickel chloride hexahydrate in step S1 are changed to 3.5 mmol and 2.1 mmol respectively, and steps S2 to S4 are retained, but steps S6 to S7 are omitted.

[0077] The photocatalysts prepared in Example 1 and Comparative Examples 1 to 8 are respectively denoted as Sv-ZIS@FNS-2 (Example 1), FNS (Comparative Example 1), ZIS (Comparative Example 2), Sv-ZIS (Comparative Example 3), Sv-ZIS@FNS-1 (Comparative Example 4), Sv-ZIS@FNS-3 (Comparative Example 5), FNS x S y -precursor (Comparative Example 6), FNS-precursor (Comparative Example 7) and FN m S n -precursor (Comparative Example 8), and tested its morphology, structure and photocatalytic performance. x S y , FNS and FN m S n FeNi x S y 、FeNi 0.48 S 1.71 andFeNi m S n Short for .

[0078] The hollow structure FeNi prepared in this comparative example 1 0.48 S 1.71 The photocatalyst was characterized by inductively coupled plasma mass spectrometry (ICP-MS), and the atomic ratio of iron, nickel and sulfur was 1:0.48:1.71, as shown in Table 1.

[0079] Table 1 Element contents of samples prepared in Comparative Example 1

[0080]

[0081] Figure 1 The electron spin resonance spectra (ESR) of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 3 of the present invention show that Example 1 and Comparative Example 3 show obvious ESR peaks, indicating that Sv-ZIS@FNS-2 and Sv-ZIS samples have abundant sulfur vacancies. However, due to the small amount of thioacetamide in Comparative Example 2, there are fewer sulfur vacancies, resulting in Figure 1 The ESR peak of Comparative Example 2 is very weak.

[0082] Figure 2The scanning electron microscope (SEM) morphology of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 8 of the present invention, wherein (a), (b), (c), (d), (e), (f), (g), (h) and (i) are SEM images of the photocatalytic materials prepared in Comparative Examples 6 to 8, Comparative Examples 1 to 4, Example 1 and Comparative Example 5, respectively. It can be seen that as the Fe:Ni ratio in the precursor decreases, the size of the precursor becomes smaller and smaller, and when the Fe content is large (Comparative Example 6), the precursor exhibits a rough surface and a non-uniform size morphology. When the Fe:Ni dosage is 3:1 (Comparative Example 7), the sample exhibits a moderate size and a uniform spherical morphology, and when the Ni content is large (Comparative Example 8), the size of the sample is generally less than 100nm, so the subsequent composite experiment is carried out using a material ratio of Fe:Ni=3:1. The FNS sample (Comparative Example 1) has a hollow structure and a uniform size of about 500 to 800nm. The ZIS (Comparative Example 2) and Sv-ZIS (Comparative Example 3) samples all show flower-like structures formed by self-assembly of nanosheets, indicating that the introduction of sulfur vacancies does not affect the morphology of the samples. Samples such as Sv-ZIS@FNS-1 (Comparative Example 4), Sv-ZIS@FNS-2 (Example 1) and Sv-ZIS@FNS-3 (Comparative Example 5) show a special three-dimensional spatial structural morphology of Sv-ZIS nanoflowers closely grown on the surface of hollow spherical FNS. This close contact indicates that a heterojunction may be formed at the interface of the composite sample.

[0083] Figure 3 Energy dispersive spectrometer (EDS) of the photocatalytic material prepared in Example 1 of the present invention. It can be seen that the sample has typical characteristic peaks of elements such as Fe, Ni, Zn, In and S.

[0084] Figure 4 The morphology and element distribution diagram of the photocatalytic material prepared in Example 1 of the present invention, wherein (a), (b) and (c) are transmission electron microscopy (TEM), element distribution diagram and high-resolution transmission electron microscopy (HRTEM) morphology diagram of the photocatalytic material prepared in Example 1, respectively. As can be seen from Figure (a), the Sv-ZIS@FNS-2 sample is hollow inside, and extremely thin nanosheets grow on the surface of the FNS nanospheres. In addition, elements such as Fe, Ni, Zn, In and S are evenly distributed. There is a clear lattice boundary between Sv-ZIS and FNS. The lattice spacing on the left side of the HRTEM image is 0.32nm, which corresponds to the (102) crystal plane of Sv-ZIS, and careful observation shows that there are many sulfur vacancies. The right side represents the FNS lattice fringes, and its spacing of 0.2nm corresponds to the (102) crystal plane.

[0085] Figure 5Figure 1 is a graph showing the photocatalytic performance of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 5, wherein (a) and (b) are graphs showing the photocatalytic hydrogen production and tetracycline hydrochloride degradation curves of the photocatalytic materials prepared in Example 1 and Comparative Examples 1 to 5, respectively. It can be seen that under the synergistic effect of sulfur vacancies and heterojunctions, the photocatalytic performance of the Sv-ZIS@FNS composite sample is greatly improved, and the Sv-ZIS@FNS-2 sample prepared in Example 1 has a photocatalytic performance of 3113.2 μmol h -1 g -1 The maximum hydrogen production rate and 1.59h -1 The highest tetracycline hydrochloride degradation rate. Although Comparative Examples 4 and 5 also have special three-dimensional spatial structural morphology of Sv-ZIS nanoflowers tightly grown on the surface of hollow spherical FNS, the hydrogen production rates of Comparative Examples 4 and 5 are significantly lower than the hydrogen production rate of Example 1, and the degradation rate of tetracycline hydrochloride is also significantly lower than the degradation rate of Example 1, indicating that the amount of FNS needs to be in an appropriate range to obtain a higher hydrogen production rate and degradation rate.

[0086] Figure 6 X-ray diffraction (XRD) patterns of the photocatalytic material prepared in Example 1 before and after photocatalytic hydrogen production and tetracycline hydrochloride degradation. It can be seen that the characteristic peaks of the Sv-ZIS@FNS-2 sample have almost no change before and after the photocatalytic hydrogen production and tetracycline hydrochloride degradation reactions, which indicates that the structure of the sample has not changed during this process, that is, the sample has good cyclic reaction stability.

[0087] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A sulfur-vacancy-rich ZnIn2S4@FeNi 0.48 S 1.71 Heterojunction photocatalyst, characterized in that In order to in situ grow ZnIn2S4 nanosheets containing sulfur vacancies on FeNi 0.48 S 1.71 On the surface of hollow nanospheres, sulfur-rich vacancies ZnIn2S4@FeNi with hollow structures are formed. 0.48 S 1.71 Heterojunction composite materials.

2. A sulfur-rich vacancy ZnIn2S4@FeNi according to claim 1 0.48 S 1.71 Heterojunction photocatalyst, characterized in that The size of the ZnIn2S4 nanosheet is 200-1000 nm, and the thickness of the nanosheet is 15-25 nm; And / or, the FeNi 0.48 S 1.71 The size of the hollow nanospheres is 300 to 1000 nm, and the hollowness degree of the hollow nanospheres is 85% to 90%; And / or, the size of the photocatalyst is 500-2000 nm.

3. A sulfur-vacancy-rich ZnIn2S4@FeNi according to any one of claims 1 to 2 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: include: Preparation of FeNi 0.48 S 1.71 Hollow nanospheres: Using ferrous chloride tetrahydrate, nickel chloride hexahydrate, polyvinyl pyrrolidone, sulfur powder and thiourea as raw materials, react at 120-150°C for 6-9 hours to obtain black powder, and then calcine the black powder under inert gas protection, keep it at 320-350°C for 3-4 hours, then heat it to 580-610°C and keep it for 3-4 hours to obtain FeNi 0.48 S 1.71 Hollow nanosphere materials; FeNi 0.48 S 1.71 The hollow nanospheres were added to the acid solution, followed by zinc chloride, indium chloride tetrahydrate and thioacetamide to obtain a solid-liquid mixture, which was reacted at 80-90°C for 2-3h in an oil bath to obtain sulfur-rich vacancy ZnIn2S4@FeNi with a hollow structure. 0.48 S 1.71 Heterojunction photocatalytic materials.

4. A sulfur-vacancy-rich ZnIn2S4@FeNi according to claim 3 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: Preparation of FeNi 0.48 S 1.71 When preparing hollow nanospheres, first dissolve ferrous chloride tetrahydrate and nickel chloride hexahydrate in ethylene glycol, stir and dissolve to obtain solution ①; Then add polyvinyl pyrrolidone to solution ①, dissolve by ultrasonication and stirring to obtain solution ②; Add sulfur powder and thiourea to solution ②, stir and dissolve to obtain solution ③; The solution ③ is reacted at 120-150°C for 6-9h, cooled naturally, centrifuged, washed and dried to obtain a black powder.

5. A sulfur-vacancy-rich ZnIn2S4@FeNi according to claim 4 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: The molar ratio of ferrous chloride tetrahydrate to nickel chloride hexahydrate is 3:(1-1.5), and the concentration of metal ions in the solution ① is 0.05-0.1 mol / L.

6. A sulfur-rich vacancy ZnIn2S4@FeNi according to claim 4 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: The average molecular weight of the polyvinyl pyrrolidone is 40,000, and the content of polyvinyl pyrrolidone in the solution ② is 5 to 10 g / L.

7. A sulfur-vacancy-rich ZnIn2S4@FeNi according to claim 4 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: The molar ratio of iron ions, nickel ions, sulfur powder and thiourea in solution ③ is 3:(1~1.5):(1~3.5):(4.5~7).

8. A sulfur-vacancy-rich ZnIn2S4@FeNi according to claim 3 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: The heating rate during calcination of the black powder is 3-6°C / min.

9. A sulfur-vacancy-rich ZnIn2S4@FeNi according to claim 3 0.48 S 1.71 A method for preparing a heterojunction photocatalyst, characterized in that: The pH value of the acid solution is 2-4, and the FeNi 0.48 S 1.71 The mass ratio of zinc chloride to indium chloride is (0.3-1):2, and the molar ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:2:(4.5-16); Preferably, FeNi is prepared 0.48 S 1.71 For hollow nanospheres, the reaction is carried out at 120-150°C for 6-9 hours, then naturally cooled, centrifuged, washed and dried; the solid-liquid mixture is reacted at 80-90°C for 2-3 hours in an oil bath, then naturally cooled, washed and dried; The washing is to use deionized water and anhydrous ethanol to wash the sample alternately for 3 times or more, the drying temperature is 60-90° C., and the drying time is 8-12 hours.

10. Use of the catalyst according to any one of claims 1 to 2 or the catalyst obtained by the method according to any one of claims 3 to 9 in photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants.

Citation Information

Cited By

  • MnIn2S4-coated Co9S8 heterojunction photocatalyst as well as preparation method and application thereof

    CN120571601A

  • Defect-regulated Cu2O photocatalyst as well as preparation method and application thereof

    CN121422965A